Large deviations for impulsive processes in the scheme of Poisson approximation - Samoilenko, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
Asymptotic analysis of the large deviation problem for impulsive processes in the scheme of Poisson approximation isperformed. Large deviations for impulsive processes in the scheme of Poisson approximation are defined by an exponentialgenerator for a jump process with independent increments.